Dialogue in a learning process: problematization of gender and gender equality in higher education. Issue 4 (4th July 2017) - Albinsson, Gunilla; Arnesson, Kerstin
Abstract: The overall aim with the study was to describe the knowledge building that was developed in a group of students who were trained nurses enrolled in a Swedish higher education programme. With a point of departure in an interactive research approach, the authors applied the dialogue seminar as method and pedagogical model. When the students in close to practice talks, shared their thoughts about how gender and gender equality could be experienced and understood, the dialogue seminar became useable. At the analysis of the stories which the students shared at the dialogue seminars, it became clear that most of the students had an ambivalent approach to gender equality. When they reflected on gender relations, they brought out the hierarchical and separate gender relations which they experienced as existing within healthcare. Furthermore, their professional lives seemed to be embedded in gender-related practices. An important conclusion is that the students' reflections oscillated between critical reflection on conditions and critical reflection on processes within their own practice in healthcare. Another finding was that the students' reflections in dialogue form became important in a learning process, not least in the light of that gender relations and gender equality only to a limited degree had been included in their nurse's education at the basic level.